PENERAPAN MODEL PEMBELAJARAN KOOPERATIF QUESTION STUDENT HAVE UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROLISIS GARAM DI KELAS XI SMAN 1 BUKIT BATU KABUPATEN BENGKALIS - Rina Annisa; Erviyenni Erviyenni; Armiyus Thaib (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : The purpose of this research is to increase student achievement on the subject of salt hydrolysis in class XI SMAN 1 Bukit Batu Kabupaten Bengkalis. Form of research is experiment research with pretest-posttest design. The sample consisted of two classes. Experiment class was given implementing model cooperative learning Question Student Have, while the control class was not given implementing model cooperative learning Question Student Have. The t-test is used for data analysis technique. Based on the final results of data processing using t-test formula with dk=39 and ɑ =0,05 obtained tarithmetic > ttable (2.75 > 1.68) means that the application of model cooperative learning Question Student Have can improve student’s achievement on the subject of salt hydrolysis in class XI SMAN 1 Bukit Batu Kabupaten Bengkalis. The improvement of student’s achievement in experiment class was supported by N-Gain score 0,74 that included in high category. Key Words : Question Student Have, Learning Achievement, Salt Hydrolysis